Horseradish Peroxidase-Catalyzed Coloration of Natural Phenols on Silk Fabric: Effects of Various Buffer Systems and pH Value on Dyed Color - Na-Won Baek; Jiang-Fei Lou; Jie Wang; Xue-Rong Fan (Journal of Natural Fibers, 2022)
Currently, the known possible shades obtained for coloring silk fabrics using enzyme catalysts such as peroxidase are limited to a few shades of brownish tint. For the oxidative dyeing method using horseradish peroxidase (HRP) to become common, it must be able to produce a more diverse range of colors; this is a problem that must be solved. The purpose of this study is to obtain various colors by dyeing natural phenolic substrates using HRP in various buffers (acetate, citrate, phosphate buffer) and various pH levels (3 ~ 9). We emphasized color diversity, which was achieved through the exploration of six different natural aromatic compounds: gallic acid (GA), guaiacol (GAC), p-coumalic acid (CA), ferulic acid (FA), catechol (CAC) and caffeic acid (CFA). We also performed a methodological survey of reaction processing parameters. The colored products generated through HRP catalysis were analyzed using UV-vis. The color of the dyed fabrics was analyzed using the CIE L*a*b* color space system. As a result of the experiment, we obtained silk fabrics with various color depths from each buffer system. This suggests that the desired color and tone of dyed silk fabrics can be achieved by adjusting the buffer system and pH value.